Study of the age of grafted larvae on some morphological characteristics of queen honey bees (Apis mellifera) - Sri Minarti; Puji Akhiroh (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2021)
Queen bees are castes in the colony tasked with producing eggs to survive a bee colony. The Queen is the only one tail in the colony and can produce eggs to be a prospective queen bee, worker and stud. The eggs of would-be queen bees and would-be worker bees are fertilized fertile eggs. The fertilization process occurs shortly before the egg is laid inside the base of the hive so that when hatching, the larvae of the would-bees Queen and prospective worker bees are the same. Honeybee cultivation, in general, still relies on conventional means, especially in the development of queen populations as well as bee populations within colonies. Beekeepers still rely heavily on the rejuvenation of queen bees through natural means by relying on colonies to not optimal the time and results obtained. The short-term goal is to get quality queen bees with the best morphol-ogy mass and quickly through grafting worker larvae. The long-term goal is to assist farmers in the procurement of quality queen bees in a mass and fast way as needed with optimal results. Method : (1). Make a queen by grafting worker larvae then developed inside a particular colony until becoming an individual to get the queen bee. (2) Devel-op grafting queen bees to get the best production.